Peningkatkan Kemampuan Guru Dalam Menyusun RPP Satu Lembar Melalui Bimbingan Pelatihan Digital Di Sekolah Binaan 2020 (Universitas Pamulang, 2021)
ABSTRACTThis study aims to improve the ability of teachers in the preparation of lesson plans that are effective, efficient and student-oriented. The research subjects were 100 teachers at the target schools. Data collection techniques were carried out with documentation, digital training attendance lists, RPP supervision instruments and analysis instruments for the results of RPP preparation. The method used is descriptive qualitative method, using the percentage technique to see the increase that occurs from cycle to cycle. The results of observations and assessments showed that there was a significant increase in the ability of teachers after digital guidance and training was implemented. The results obtained in the initial conditions were 100 teachers 9.79% who were able to prepare lesson plans. Increased in cycle 1 an average of 61.12%, then cycle 2 measures increased by an average of 82.70%. The explanation of the initial conditions is that it does not increase to enough and is good in cycle 2. The conclusion is that the training through digital is stated to have succeeded in increasing the ability of teachers to prepare lesson plans that are effective, efficient and oriented to the success of learning for students at the target schools in South Tangerang City.Keywords: Ability; RPP; Digital Tutoring. ABSTRAKPenelitian ini bertujuan untuk meningkatkan kemampuan guru dalam penyusunan RPP yang efektif, efesien dan berorientasi pada peserta didik. Subyek penelitian 100 guru pada Sekolah Binaan. Teknik pengumpulan data dilakukan dengan dokumentasi, daftar kehadiran bimlat digital, instrumen supervisi RPP dan instrument analisis hasil penyusunan RPP. Metode yang digunakan adalah metode deskriptif kualitatif, dengan menggunakan teknik persentase untuk melihat peningkatan yang terjadi dari siklus ke siklus. Hasil observasi dan penilaian menunjukkan terjadi peningkatan kemampuan guru secara signifikan setelah dilaksanakan bimbingan dan pelatihan digital. Hasil yang diperoleh kondisi awal sebanyak 100 guru 9,79% yang mampu menyusun RPP. Meningkat pada sikulus 1 rerata 61,12%, kemudian tindakan siklus 2 meningkat rerata 82,70%. Penjelasan dari kondisi awal adalah kurang meningkat menjadi cukup dan baik pada siklus 2. Kesimpulannya adalah bimlat melalui digital dinyatakan berhasil meningkatkan kemampuan guru dalam penyusunan RPP yang efektif, efesien dan berorientasi pada keberhasilan belajar peserta didik pada sekolah binaan Kota Tangerang Selatan.Kata kunci: Kemampuan; RPP; Bimbingan Pelatihan Digital.